å¤ç”¸é«˜ä¸ç¬¬ä¸‰å›½ç«‹å¦æ ¡äºŒå¹´çº§å¦ç”Ÿä½¿ç”¨â€œæ˜¯â€¦çš„â€å¥å¼çš„ åè¯¯åˆ†æž - Oktaviani, Ditha; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
?????...??????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? ??????????? ???? ???? Abstract:"Shi ... de " is one type of sentence pattern predicated verb, serves to emphasize related to verb, for example, used to emphasize time, place,manner, conditions, objectives, objects, equipment and so on. It is also used to emphasize the person doing the action, emphasizes the object that affected by the action; and emphasizes actions that produce a reaction. From the explanation, we can conclude that the pattern of the phrase " shi ... de " is very important. But the author found  that the student of 11th grade of SMA Negeri 3 Pontianak did not fully understand on how to use the sentence patterns " shi ... de ", so some missapplication still happened.The author used the questionnaire method, and do the analysis of the students' mistakes in using pattern of the phrase " shi ... de ".   Keywords:Pattern phrase " shi ... de " Error Analysis The Cause Of The Error